Alien Hand Sign and Other Cognitive Deficits following Ruptured Aneurysm of the Anterior Communicating Artery - Alan J. Parkin; Caroline Barry (Behavioural Neurology)
We describe a right-handed patient who suffered a ruptured aneurysm of the anterior communicating artery (ACoA) which was clipped successfully. Computerized tomography indicated a low density area in the genu of the corpus callosum and the infero-lateral aspect of the left frontal lobe. On recovery the patient's most notable deficit was the “alien hand sign” whereby the left hand would frequently interfere with the actions of the right hand. Problems in response initiation were also evident. There was significant memory loss and performance was impaired on some tests of frontal lobe function. Discussion centres on the functional locus of the alien hand sign but other aspects of the patient's deficits are also considered.